The process of weakening of nation-state in the era of neo-liberalism and the crisis of democracy - Stamenova, Svetlana D. (Sociološki pregled, 2021)
The article aims to show that as a result of globalization and neo-liberal form of governance and ideology, the state was weakened through a complex system of economic, financial, technological and social relations on a global scale. The withdrawal of the state from regulative functions on its territory is a refusal of the state for ideological mobilization of its populace based on nationalism and national identity. During the decline of national identity, the national state moves its role from imposing of cultural and national homogeneity, a characteristic of the earlier stage of nation-state building, to supporting cultural diversity. Crisis of democracy and emergence of post-democracy are considered and the question about possibility of having democracy beyond the nation-state borders.